Authorized Honesty: The World Is What It Is: The Authorized Biography of V. S. Naipaul - Idris, Farhad Bani (EAST WEST JOURNAL OF HUMANITIES, 2013)
No acquaintance of V. S. Naipaul could possibly imagine that during the scattering of Pat Naipaul’s ashes, the Quran was recited, but the author, highly acclaimed for both his ﬁction and non-ﬁction but also known for his hostility towards Islam, allowed the lapse and was even grateful. The recitation of Sura Fatiha in Arabic was performed by Naipaul’s newly-wed wife Nadira, a Muslim woman from Pakistan with links in Kenya. Naipaul was too distraught to accompany her into the woods on Cooper’s Hill; he stood by the car, crying the entire time. The location, near Gloucester, had memories for him, memories of Pat, wife of a forty-one year long marriage. Months earlier, the funeral at Salisbury Crematorium was austere and frugal. Curiously enough, Naipaul defended the minimalism to someone in Islamic terms: “’It was chaste, it was Quranic in its purity’” (480). There was no decent interval between the ﬁrst wife’s death and the second wedding. Naipaul had met Nadira in Pakistan while collecting materials for a new book on Islam (Beyond Belief) and had proposed to her when Pat was still alive but dying of cancer. She passed away in February of 1996; the wedding occurred in April; Pat’s remains were dispersed in October.